FEMa-FS: Finite Element Machines for Feature Selection - Biaggi, Lucas [UNESP]; Papa, Joao P. [UNESP]; Costa, Kelton A. P [UNESP]; Pereira, Danillo R.; Passos, Leandro A. (Institute of Electrical and Electronics Engineers (IEEE), 2022)
Identifying anomalies has become one of the primary strategies towards security and protection procedures in computer networks. In this context, machine learning-based methods emerge as an elegant solution to identify such scenarios and learn irrelevant information so that a reduction in the identification time and possible gain in accuracy can be obtained. This paper proposes a novel feature selection approach called Finite Element Machines for Feature Selection (FEMa-FS), which uses the framework of finite elements to identify the most relevant information from a given dataset. Although FEMa-FS can be applied to any application domain, it has been evaluated in the context of anomaly detection in computer networks. The outcomes over two datasets showed promising results.
Keywords: Computer Networks Security; Feature Selection; Finite Element Method; Machine Learning